ANALYSIS OF THE EXPERIENCES OF USING MONITORING AND EVALUATION SYSTEM IN SERVICE DELIVERY AMONG LOCAL AUTHORITIES IN RWANDA: A CASE OF SECTOR COUNCILS IN GASABO DISTRICT - Nyirarukundo, Diane; Nzyuko, Dr. Solomon; Korir, Dr. Agnes (Journal of Public Policy and Administration, 2017)
Purpose: To analyze the experience of using monitoring and evaluation system in service delivery among local authorities in Rwanda. Methodology: The study adopted a descriptive research design. Findings: The findings revealed that most sectors have an established monitoring and evaluation system. The results on the role of monitoring and evaluation in service delivery revealed that monitoring and evaluation enhances effective use of resources in their sector through use of performance contracts. Findings also showed that the local government of Gasabo district faced the challenge of inadequate finances in monitoring and evaluation of service delivery, lack of expertise in monitoring and evaluation of service delivery, lack of capacity in monitoring and evaluation of service delivery, high level of bureaucracy in monitoring and evaluation of service delivery and existence of multiple M&E frameworks. The results also revealed that the local government of Gasabo District experienced ease in making policies due to use of monitoring and evaluation system in service delivery, proper management, transparency and accountability, empowerment of the people of Rwanda to actively participate in the political and social and economic transformation of Rwanda. Unique contribution to theory, practice and policy: Gasabo District in Rwanda will benefit from the study findings in that the study findings will assist in setting clear benchmark on how to establish regulations that will provide the direction, oversight and assistance to those involved in service delivery. The study findings will also benefit the Rwandan citizens, in the long run in that they will enjoy proper services and at their convenient timing as stipulated in the district development plans. The findings of this study will also enable the government/concerned authorities come up with measures on how to overcome the loop holes in service delivery and how such measures could contribute to successful better service delivery in other districts of Rwanda and other countries. Lastly, the findings will be useful to academicians and other researchers and policy makers and will contribute to existing literature for further research to extend, refine or validate the findings of the study.